Animated Video Anemia Education and its Effect on Iron Tablet Adherence and Hemoglobin Levels among Female Adolescents at SMPN 17 Samarinda - Febry Dwistika, Wulan; Dwi Utami, Kurniati; Anshory, Jamil (Journal of Law and Social Politics, 2024)
Background: Adolescent girls are at high risk of anemia. Health screening in 2021 showed that 46.15% of adolescent girls at SMPN 17 Samarinda were at risk of anemia. Limited knowledge and low awareness remain major challenges in anemia prevention and management. Objective: This study aimed to examine the effect of anemia education using animated videos on adherence to iron tablet consumption and hemoglobin levels among adolescent girls at SMPN 17 Samarinda. Methods: This quantitative study employed a quasi-experimental pretest–posttest control group design. A total of 36 respondents were selected using purposive sampling and divided into an experimental group receiving animated video education (n = 18) and a control group receiving leaflet-based education (n = 18). The study was conducted from May to July 2023. Data were collected using the MMAS-8 questionnaire to assess adherence and hemoglobin level measurements. Data were analyzed using Wilcoxon and Mann–Whitney tests with a significance level of ? = 0.05. Results: The experimental group showed significant improvements in iron tablet adherence (p = 0.000) and hemoglobin levels (p = 0.000). In the control group, adherence increased significantly (p = 0.000), but no significant change in hemoglobin levels was observed (p = 0.112). Significant differences between groups were found for adherence (p = 0.002) and hemoglobin levels (p = 0.001). Conclusion: Animated video–based anemia education was more effective than leaflet-based education in improving adherence to iron tablet consumption and hemoglobin levels among adolescent girls. Future studies should include assessments of iron-rich dietary intake to obtain more comprehensive findings